A sputnik moment? The Natural Sciences and Humanities.An interview with Edward L.Ayers - Peter Vale (South African Journal of Science)
Fifty years ago,the Natural Sciences and the Humanities were described (byC.P. Snow) as'TwoCultures'. Are they still so? This interview conducted by Peter Vale suggests that they are complementary and are likely to be increasingly so. Edward Ayers is the President of the University o fRichmond. Previously dean of arts and sciences at the University of Virginia, where he began teaching in 1980,Ayers was named the National Professor of the Year from the Carnegie Foundation for the Advancement of Teaching in 2003. A historian of the American South, Ayers has written and edited ten books. The Promise of the New South: Life After Reconstruction was a finalist for both the National Book Award and the Pulitzer Prizein1992. In the Presence of Mine Enemies, War in the Heart of America 1859 - 1863 won the 2003 Bancroft Prize for distinguished writing in American history and the Beveridge Prize for the best book in English on the history of the Americas since 1492. Ayersisa former president of the US National Council on the Humanities, and has been elected to the American Academy of Arts and Sciences